TRPM6 and TRPM7: Novel players in cell intercalation during vertebrate embryonic development. Issue 8 (26th May 2020) - Runnels, Loren W.; Komiya, Yuko
Abstract: A common theme in organogenesis is how the final structure of organs emerge from epithelial tube structures, with the formation of the neural tube being one of the best examples. Two types of cell movements co‐occur during neural tube closure involving the migration of cells toward the midline of the embryo (mediolateral intercalation or convergent extension) as well as the deep movement of cells from inside the embryo to the outside of the lateral side of the neural plate (radial intercalation). Failure of either type of cell movement will prevent neural tube closure, which can produce a range of neural tube defects (NTDs), a common congenital disease in humans. Numerous studies have identified signaling pathways that regulate mediolateral intercalation during neural tube closure. Less understood are the pathways that govern radial intercalation. Using the Xenopus laevis system, our group reported the identification of transient receptor potential (TRP) channels, TRPM6 and TRPM7, and the Mg 2+ ion they conduct, as novel and key factors regulating both mediolateral and radial intercalation during neural tube closure. Here we broadly discuss tubulogenesis and cell intercalation from the perspective of neural tube closure and the respective roles of TRPM7 and TRPM6 in this critical embryonic process. Key Findings: Cell intercalation is one of the most important cell movements during neural tube closure. Depending on the direction and plane of cell movement, intercalation can be divided into two types: mediolateral and radial intercalation. Our research has uncovered that ion channel TRPM7 chiefly contributes to mediolateral intercalation in dorsal ectoderm and mesoderm at early gastrulation and in neural cells at the midline during early neurulation, whereas TRPM6 mainly influences radial intercalation in non-neural cells in lateral tissues later during neurulation. In this review, we will describe how cell intercalation contributes to neural tube closure and highlight the molecular mechanisms controlling cell intercalation, including our discovery of the unique roles that Mg 2+ and TRPM6 and TRPM7 ion channels play in this critical process.